2012
DOI: 10.1590/s1984-82502012000100019
|View full text |Cite
|
Sign up to set email alerts
|

Activity of antiretroviral drugs in human infections by opportunistic agents

Abstract: Highly active antiretroviral therapy (HAART) is used in patients infected with HIV. This treatment has been shown to significantly decrease opportunist infections such as those caused by viruses, fungi and particularly, protozoa. The use of HAART in HIV-positive persons is associated with immune reconstitution as well as decreased prevalence of oral candidiasis and candidal carriage. Antiretroviral therapy benefits patients who are co-infected by the human immunodeficiency virus (HIV), human herpes virus 8 (HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…and Cryptococcus spp. 19,20 . Indeed, several groups have shown that these HIV-PIs are effective in inhibiting the in vitro growth of several fungi, including F. pedrosoi, Cryptococcus neoformans Candida albicans and Trichosporon asahii 13,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…and Cryptococcus spp. 19,20 . Indeed, several groups have shown that these HIV-PIs are effective in inhibiting the in vitro growth of several fungi, including F. pedrosoi, Cryptococcus neoformans Candida albicans and Trichosporon asahii 13,[21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…It results in an atherogenic lipid profile, which has the well-defined characteristics of chronic diseases [1,2]. In addition to dyslipidemia, there is also glucose intolerance, diabetes mellitus type II and elevated low density lipoprotein cholesterol (LDL-C), which are proven risk factors for cardiovascular diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) has been available since 1996 for individuals diagnosed with AIDS and has allowed long-term control of the disease with increased survival (4) (5) and decreased morbidity and mortality rates (5) . However, AIDS has become a chronic and degenerative disease for patients undergoing ART (1) (2) (6) .…”
mentioning
confidence: 99%